Theological Perspectives on Responses to Prayer Requests in WhatsApp Groups - Sostenis Nggebu; Yopie F.M. Buyung; Alan Wood (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2023)
The problem of this article speaks the importance of the essence of prayer in the Christian life. Praying is a valuable opportunity for believers. Humans can ask God for help with their life problems. Praying can be seen as a special place for believers to build close relationships with God. They can also utilise any technology service to connect and pray for each other such as through calling, sending letters or newsletters, and WhatsApp Group contemporary communication facilities. Through praying for each other, people are interconnected and dependent on God. The method used in this study is a descriptive method. Researchers investigate the text of Bible verses related to the importance of praying for others. This approach is taken to lay the Christian theological basis of prayer. The results show that praying for others is a Christian character. Because Christians are commanded by Christ to pray for each other. Praying for others reflects a Christian character that is firmly inherent in believers. Believers who submit prayer support show the plea is urgent and urgent. That need must be answered by responding and praying for it. In today's context, WhatsApp Group facilities can be used as an effective and communicative means to convey prayer requests to and from others. The request encourages believers with sincere hearts to be enterprising and pray for each other.